Contribution of Non-canonical Cortisol Actions in the Early Modulation of Glucose Metabolism of Gilthead Sea Bream (Sparus aurata) - Aedo, Jorge E.; Ruiz-Jarabo, Ignacio; Martínez-Rodríguez, Gonzalo; Boltaña, Sebastián; Molina, Alfredo; Valdés, Juan A.; Mancera, Juan M. (Frontiers in Endocrinology, 2019)
Teleost fish are exposed to diverse stressors in farming and wildlife conditions during their lifespan. Cortisol is the main glucocorticoid hormone involved in the regulation of their metabolic acclimation under physiological stressful conditions. In this context, increased plasma cortisol is associated with energy substrate mobilization from metabolic tissues, such as liver and skeletal muscle, to rapidly obtain energy and cope with stress. The metabolic actions of cortisol have primarily been attributed to its genomic/classic action mechanism involving the interaction with intracellular receptors, and regulation of stress-responsive genes. However, cortisol can also interact with membrane components to activate rapid signaling pathways. In this work, using the teleost fish gilthead sea bream (Sparus aurata) as a model, we evaluated the effects of membrane-initiated cortisol actions on the early modulation of glucose metabolism. For this purpose, S. aurata juveniles were intraperitoneally administrated with cortisol and with its membrane impermeable analogue, cortisol-BSA. After one and six hours of each treatment, plasma cortisol levels were measured, together with glucose, glycogen and lactate in plasma, liver and skeletal muscle. Transcript levels of corticosteroids receptors (gr1, gr2 and mr) and key gluconeogenesis (g6pc and pepck)- and glycolysis (pgam1 and aldo) related genes in the liver were also measured. Cortisol and cortisol-BSA administration increased plasma cortisol levels in S. aurata one hour after administration. Plasma glucose levels enhanced six hours after each treatment. Hepatic glycogen content decreased in the liver at one hour of both cortisol and cortisol-BSA administration, while increased at six hours due to cortisol but not in response to cortisol-BSA. Expression of gr1, g6pc, pgam1 and aldo were preferentially increased by cortisol-BSA in the liver. Taking all these results in consideration, we suggest that non-canonical cortisol mechanisms contribute to the regulation of the early glucose metabolism responses to stress in S. aurata.